Positive permanent charge in oxisols - Tessens, E.; Zauyah, Siti (Wiley, 1982)
The existences of a positive permanent charge can be inferred from charge characteristics of highly weathered tropical soils; it was found to be related to isomorphous substitution of Ti(IV) for Fe(III) in iron oxides. Comparable near‐constant values were found from anion adsorption at pH 7.0 to 9.0. It was concluded that both positive and negative permanent charge can coexist in the same soil.